1998
DOI: 10.1038/emm.1998.22
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine causes glycerophosphorylcholine accumulation through ryanodine-inhibitable increase of cellular calcium and activation of phospholipase A2 in cultured MDCK cells

Abstract: Glycerophosphrylocholine (GPC) is a renal medullary compatible organic osmolyte that is derived from choline via phosphatidylcholine, which is catalyzed in part by phospholipase A 2 ( P L A 2 ) and its degradation by GPC:choline phosphodiesterase (GPC:choline PDE). We found that caffeine elevated intracellular free calcium (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…In the present study, various doses of caffeine (from 1 μM to 10 mM) were used to study the protective mechanisms of caffeine at early phases of COM kidney stone formation, including crystallization, crystal growth, and crystal-cell adhesion28. This range of caffeine dosage was chosen based on the urinary caffeine concentrations measured after 3-h of caffeinated beverage ingestion293031, as well as concentrations used in previous studies on effects of caffeine on the kidney3233. Previous studies have demonstrated that caffeine increased urinary excretion of citric acid34, which is considered as one among several COM crystal growth inhibitors, but on the other hand enhanced urinary calcium excretion9343536.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, various doses of caffeine (from 1 μM to 10 mM) were used to study the protective mechanisms of caffeine at early phases of COM kidney stone formation, including crystallization, crystal growth, and crystal-cell adhesion28. This range of caffeine dosage was chosen based on the urinary caffeine concentrations measured after 3-h of caffeinated beverage ingestion293031, as well as concentrations used in previous studies on effects of caffeine on the kidney3233. Previous studies have demonstrated that caffeine increased urinary excretion of citric acid34, which is considered as one among several COM crystal growth inhibitors, but on the other hand enhanced urinary calcium excretion9343536.…”
Section: Resultsmentioning
confidence: 99%
“…In pigmented ciliary epithelial cells [30] and bovine chromaffin cells [31] PLA2-inhibition prevents the activation of the RVDC. In MDCK cells PLA2 is also involved in the synthesis of the organic osmolyte glycerophosphorylcholine (GPC) that is derived from choline via PC and its activation appears to result from a caffeine sensitive, ryanodineinhibitable increase of Ca i [32].…”
Section: Arachidonic Acid and Eicosanoidsmentioning
confidence: 99%
“…Hence, the caffeine-dependent intracellular signalling pathway in this organism is assumed to be independent of the caspase-dependent apoptotic signalling found in mammalian cells. Furthermore, stimulation with high concentrations of caffeine has been reported to cause a greater than 4-fold increase in AA levels in a mammalian culture cell-line8. Therefore, we measured the survival rate in Hela cells in the presence of the cell-permeable general caspase inhibitor, Q-VD-OPh9 (Fig.…”
Section: Resultsmentioning
confidence: 99%